The effect of luck perception on intertemporal decision-making: the mediating role of decision confidence and the moderating role of self-construal - Zhong, Hao; Wang, Yuwei; Li, Yanxia (Frontiers in Psychology, 2025)
Lucky cues represent a common yet subtle situational stimulus in daily life. They can instill confidence and optimism in individuals, enabling them to seize opportunities and address challenges effectively. Moreover, lucky cues significantly influence consumption behaviors, diversity seeking, novelty pursuit, and risk-taking tendencies. However, prior studies have rarely examined luck within uncertain contexts or integrated its unique positive psychological resources to explore its effects on intertemporal decision-making. To address this gap, we conducted three experimental studies to investigate the relationship between individual luck perception and intertemporal decision-making from an uncertain intertemporal perspective. We revealed that perceiving luck would enhance individuals’ tendency to choose delayed gratification in intertemporal decision-making tasks. Furthermore, decision-making confidence would mediate this effect. Specifically, compared with the bad-luck group, individuals in the good-luck condition would exhibit stronger decision confidence and demonstrate a greater preference for delayed option in intertemporal decision-making. Additionally, self-construal would moderate both the direct impact of luck perception on intertemporal decision-making and the mediating role of decision confidence. For individuals with an interdependent self-construal, luck perception would strengthen their decision confidence, making them more likely to select larger-later rewards in intertemporal decision-making. In contrast, this effect would be weaker among individuals with an independent self-construal. This study extend the understanding of luck perception in intertemporal contexts and provide practical implications for interventions in education, decision-making guidance, and psychological correction.